Novel Approach: Diphenhydramine and Lidocaine Combination Therapy for Alleviating Inflammatory and Allergic Skin Conditions with Coexisting Itch - Katarzyna Karłowicz-Bodalska; Natalia Janicka; Małgorzata Oślizło; Natalia Julia Sauer (Polskie Towarzystwo Farmaceutyczne, 2024)
Skin inflammatory and allergic conditions often result in symptoms such as erythema, edema, and pruritus, significantly impacting patients' quality of life. Traditional treatment approaches target either the inflammatory or allergic components individually, leaving the accompanying itch inadequately addressed. This study aims to explore the efficacy and safety of a combination therapy using diphenhydramine and lidocaine for managing inflammatory and allergic skin conditions with coexisting itch. Diphenhydramine, a first-generation antihistamine, exhibits potent antiallergic properties by inhibiting histamine receptors (H1). Lidocaine, a local anesthetic, possesses analgesic effects and alleviates pruritus by blocking sensory neurons and reducing capillary permeability. The synergistic effects of diphenhydramine and lidocaine hold promise in providing a comprehensive treatment option for individuals with inflammatory and allergic skin conditions. In this study, the efficacy and safety of combination therapy with diphenhydramine and lidocaine will be evaluated through its effects on symptom relief, inflammatory markers and patient satisfaction. Furthermore, we will analyze dermatoses where the combination therapy used had the best results. The study will also focus on market analysis and formulation availability. This investigation into the diphenhydramine and lidocaine combination therapy represents an innovative approach in dermatology, offering a unique solution for addressing both the underlying inflammation and the troublesome itch associated with inflammatory and allergic skin conditions.